Emancipation process: an exploratory study on accounting change process informed by middle range theory / Rasid Mail, Ruhaya Atan and Nafsiah Mohamed - Mail, Rasid; Atan, Ruhaya (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2009)
Previous authors have argued that methodological flaws in accounting research have led to a deficiency in theoretical development, and consequently a deficiency in management accounting practice. The adoption of a hard science approach and dependency on mathematical modeling has restricted accounting’s potential to solve societal and organizational problems. In considering a more critical approach to management accounting, Laughlin (1995) promoted the application of Middle Range Thinking. This approach offers an intermediate theoretical, methodological, and change approach in investigation, as compared to extreme subjectivist and positivist views. To demonstrate the use of such a position, this paper presents a case study informed by Middle Range Theory.